The Effects of Digital Media on Political Knowledge and Participation in Election Campaigns: Evidence From Panel Data. (February 2014) - Dimitrova, Daniela V.; Shehata, Adam; Strömbäck, Jesper; Nord, Lars W.
While the majority of previous research suggests there are positive relationships between digital media use and political participation and knowledge, most studies have relied on cross-sectional surveys and have thus not been able to firmly establish the chain of causality. Also, there is little research investigating use of different forms of digital media and their relative effects on political participation and knowledge. This study examines (a) the effects of digital media use on political participation and knowledge and (b) whether different forms of digital media use affect people differently. Drawing on two representative panel surveys, the study demonstrates that there are only weak effects of digital media use on political learning, but that the use of some digital media forms has appreciable effects on political participation.